Ex-Zier - A Abdul Karim, Nur Sarah Nabilah; Ali, Humaira Nasuha; Abdullah, Noor Farah Edrina; Abdullah, Noor Farah Erika; Mohd Rizal, Ruzza Ellyyana; Hashim, Nurhaslinda (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Ex-Zier is an innovative web-based platform designed to simplify and streamline export pricing. It addresses common challenges faced by exporters, small businesses, and students by offering real-time exchange rate integration, automated pricing calculations, and mobile-friendly access all in one user-friendly platform. Unlike many existing tools that are overly complex or fragmented, Ex-Zier combines key pricing components such as currency conversion, shipping costs, and estimated taxes into a single solution, reducing manual effort and pricing errors. The platform is especially valuable for small businesses and exporters operating across multiple countries, where fluctuating exchange rates and varying trade regulations often complicate pricing. With Ex-Zier, users can generate accurate and up-to-date export prices instantly, helping them remain competitive in the global market. In addition to its practical applications, Ex-Zier serves as a powerful educational tool. It helps international trade and business students apply classroom theory to real-world scenarios, deepening their understanding of global pricing strategies, cost structures, and cross-border logistics. Aspiring entrepreneurs and individuals unfamiliar with export procedures can also use the platform to gain insight into international trade, making global commerce more accessible and less intimidating. The novelty of Ex-Zier lies in the integration of essential export tools with a clean, mobile-optimized interface and real-time data. It's clear design and customizable features improve user engagement and efficiency, while its educational value supports future industry professionals. With a clear target market, strong commercialization potential, and community-focused benefits, Ex-Zier stands out as a smart, comprehensive solution that transforms how users approach export pricing in today’s fast-moving global economy.